A Dyadic Perspective of Felt Security: Does Partners’ Security Buffer the Effects of Actors’ Insecurity on Daily Commitment? - Sasaki, Eri (Int J Environ Res Public Health, 2020)
Interdependence and attachment models have identified felt security as a critical foundation for commitment by orientating individuals towards relationship-promotion rather than self-protection. However, partners’ security also signals the relative safety to commit to relationships. The current investigation adopted a dyadic perspective to examine whether partners’ security acts as a strong link by buffering the negative effects of actors’ insecurity on daily commitment. Across two daily diary studies (Study 1, N = 78 dyads and Study 2, N = 73 dyads), actors’ X partners’ daily felt security interactions revealed a strong-link pattern: lower actors’ felt security on a given day predicted lower daily commitment, but these reductions were mitigated when partners reported higher levels of felt security that day. Actors’ X partners’ trait insecurity (attachment anxiety) interaction also showed this strong-link pattern in Study 1 but not Study 2. The results suggest that partners’ felt security can help individuals experiencing insecurity overcome their self-protective impulses and feel safe enough to commit to their relationship on a daily basis.